ANOTHER EVIDENCE IN SUPPORT OF THE EARLY INTRODUCTION OF EFL IN INDONESIA - Suwartono Suwartono (Universitas Muhammadiyah Surakarta, 2006)
The English vocabulary mastery of Junior High School students had been in- fluenced by their previous experience of learning English in Elementary School. The study was aimed to examine the influence of the English learning implementa- tion in Elementary School towards the level of students’ English learning achieve- ment in the next stage, Junior High School. For convenience, four Junior High Schools were chosen as sample schools, i..e: SMP Negeri 1, SMP Negeri 8, SMP Al-Irsyad and SMP Susteran in the town of Purwokerto. This type of ex-post facto survey includes 142 students from the first year consisting of 73 students from Elementary Schools which had implemented the English teaching while 69, from schools which had not. To know their achieving of English, the students were given a test on vocabulary which was learned for the first four months. The result showsvalue critical value that using the t-test statistical tool, t-is much greater than t-or 3.0692 1. Introduction influential factor, exposure is inadequately pre- Early foreign language teaching has nowa- sented. Success in foreign language learningdays become a trend in Indonesia. In many badly needs extensive linguistic exposure as elementary schools English is taught as a com- inputs. Seen from the language pedagogical pulsory subject ranging from grades 1 to 4. perspective, the teaching of English for elemen- Everywhere, foreign language courses, kinder- tary school level students indicates the devel- gartens, and play groups offer special programs oping growing awareness of the need for giv- for young children and pre-school attendants. ing an early start in the process of learning a This is apparently a step in the right direction, second/ foreign language.since as a foreign language, English is learned There are some explanations as to why almost exclusively in classrooms, where the very learning a language is better started at a very 1.960 with 140 df, at the 5% level of significance. It means that the alternative hypothesis: “a significant difference in the mastery of Junior High School between students who had received English as a compulsory course at their elementary schooling background and those who had not exists” is confirmed. Therefore, it is statistically proven that the teaching of English at Elementary Schools contributes to the students’ English achievement. Key words: ex-post facto, achievement, early age, the t-test, and English implementa- tion.